The RF and microwave handbook. - Golio, John Michael, 1954-; Golio, Janet (Electrical engineering handbook series., 2008)
Introduction, P. Fay Microwave and RF Engineering, M. Golio Passive Technologies Passive Lumped Components, A. Riddle Passive Microwave Devices, M.B. Steer Dielectric Resonators, S.J. Fiedziuszko RF MEMS, K.R. Varian Surface Acoustic Wave (SAW) Filters, D.C. Malocha RF Coaxial Cables, M.E. Majerus Coaxial Connectors, D. Anderson Antenna Technology, J.B. West Phased Array Antenna Technology, J.B. West The Fresnel Zone Plate Antenna, J.C. Wiltse RF Package Design and Development, J.S. Pavio Active Device Technologies Varactors, J. Stake Schottky Diode Frequency Multipliers, J.R. Ea.